Hope in the water [videorecording (DVD)] - Lemmer, Thomas G.; Hirose, Lorie; Thurston, Baratunde; Stewart, Martha; Woodley, Shailene (PBS, 2024)
Marking Kelley's foray into docu-series television, HOPE IN THE WATER travels the globe to discover the creative solutions and breakthrough blue food technologies that could not only feed us but help save our threatened seas and fresh waterways. The series highlights the stories of amazing innovators, aquafarmers, and fishers who are working toward a sustainable future for the planet.